The inferior frontal sulcus: Cortical segregation, molecular architecture and function. (August 2022) - Ruland, Sabine H.; Palomero-Gallagher, Nicola; Hoffstaedter, Felix; Eickhoff, Simon B.; Mohlberg, Hartmut; Amunts, Katrin
Abstract: The inferior frontal sulcus is conceptualized as the landmark delineating ventro-from dorsolateral prefrontal cortex. Functional imaging studies report activations within the sulcus during tasks addressing cognitive control and verbal working memory, while their microstructural correlates are not well defined. Existing microstructural maps, e.g., Brodmann's map, do not distinguish separate areas within the sulcus. We identified six new areas in the inferior frontal sulcus and its junction to the precentral sulcus, ifs1-4, ifj1 - ifj2, by combined cytoarchitectonic analysis and receptor autoradiography. A hierarchical cluster analysis of receptor densities of these and neighbouring prefrontal areas revealed that they form a distinct cluster within the prefrontal cortex. Major interhemispheric differences were found in both cyto- and receptorarchitecture. The function of cytoarchitectonically identified areas was explored by comparing probabilistic maps of the areas in stereotaxic space with their functions and co-activation patterns as analysed by means of a coordinate-based meta-analysis. We found a bilateral involvement in working memory, as well as a lateralization of different language-related processes to the left hemisphere, and of music processing and attention to the right-hemispheric areas. Particularly ifj2 might act as a functional hub between the networks. The cytoarchitectonic maps and receptor densities provide a powerful tool to further elucidate the function of these areas. The maps are available through the Human Brain Atlas of the Human Brain Project and serve in combination with the information on the cyto- and receptor architecture of the areas as a resource for brain models and simulations.